Da’wah in the TikTok era: Analyzing Gus Miftah’s rhetoric, controversy, and community character education impact - Taufikin, Taufikin; Nurhayati, Sri; Muhajarah, Kurnia (Jurnal Ilmu Dakwah, 2025)
Purpose – This study aimed to examine how Gus Miftah’s TikTok-based da’wah merges rhetorical strategies, audience reaction, and Islamic character education within a dynamic digital setting. Method – Using interpretative and critical discourse analysis, the research sampled Gus Miftah’s TikTok videos, user comments, and YouTube sermons. Linguistic and rhetorical patterns were coded and triangulated to ensure analytical reliability. Result – Findings revealed that his succinct, humor-infused style successfully engaged younger audiences yet incited controversy regarding doctrinal fidelity, underscoring the delicate balance between accessibility and theological rigor in digital religious discourse. Implication – This tension highlights the need for ethical, pedagogical, and communicative recalibration, prompting religious figures to reconcile user-friendly presentation with doctrinal depth. Future efforts must address algorithmic constraints and community-driven discourse to maintain credibility. Originality/Value – The study addresses a gap by analyzing how TikTok’s algorithmic culture and participatory audience mechanics shape contemporary da’wah. It offers novel insights into how digital media redefine religious authority and communication in online contexts. *** Tujuan – Studi ini bertujuan untuk menganalisis bagaimana da’wah Gus Miftah di platform TikTok menggabungkan strategi retorika, reaksi audiens, dan pendidikan karakter Islam dalam konteks digital yang dinamis. Metode – Menggunakan analisis wacana interpretatif dan kritis, penelitian ini menganalisis video TikTok Gus Miftah, komentar pengguna, dan khotbah YouTube. Pola linguistik dan retorika dikodekan dan ditriangulasi untuk memastikan keandalan analisis. Hasil – Temuan menunjukkan bahwa gaya penyampaiannya yang ringkas dan sarat humor berhasil menarik perhatian audiens muda, namun juga memicu kontroversi terkait kesetiaan doktrinal, menyoroti keseimbangan halus antara aksesibilitas dan ketelitian teologis dalam diskursus agama digital. Implikasi – Ketegangan ini menyoroti kebutuhan akan penyesuaian etis, pedagogis, dan komunikatif, mendorong tokoh agama untuk menyeimbangkan presentasi yang ramah pengguna dengan kedalaman doktrinal. Upaya di masa depan harus mengatasi batasan algoritmik dan diskursus yang didorong oleh komunitas untuk mempertahankan kredibilitas. Orisinalitas/Nilai – Studi ini mengisi celah dengan menganalisis bagaimana budaya algoritmik TikTok dan mekanisme audiens partisipatif membentuk da’wah kontemporer. Studi ini menawarkan wawasan baru tentang bagaimana media digital mendefinisikan ulang otoritas agama dan komunikasi dalam konteks online.